Influence of amorphous raw rice husk ash as precursor and curing condition on the performance of alkali activated concrete - Thamer Alomayri (Elsevier, 2021)
The detrimental impact of Portland cement (PC) which is the primary binder in the production of cementitious materials such as concrete has called for a need to use alternative binders to produce concrete. Of such promising sustainable alternative to the conventional PC concrete (PCC) are alkali-activated concrete (AACs) which are produced by using a binder composed of an aluminosilicate precursor and alkali activator. In this study, blast furnace slag (BFS) was used as the primary precursors in the production of AACs. Amorphous raw rice husk ash (RRHA) was used at various dosages to partially replace BFS as the precursor. The corresponding influence of the RRHA content and curing conditions on the performance of AACs were evaluated. The two curing conditions utilized are ambient temperature curing and thermal curing for 24 h at 60 °C followed by ambient temperature curing. Findings from this study showed that the use of RRHA as a 10% replacement of the BFS is optimum as it yielded enhanced mechanical and durability performance. It was also found out that the thermal curing of AACs for 24 h before curing at ambient temperature is beneficial to improving the performance.